2021
DOI: 10.3389/fonc.2021.714866
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes Related to Liver Metastasis of Colorectal Cancer by Integrative Analysis

Abstract: Liver metastasis of colorectal cancer (LMCRC) severely damages patient health, causing poor prognosis and tumor relapse. Marker genes associated with LMCRC identified by previous study did not meet therapeutic demand. Therefore, it is necessary to identify new biomarkers regulating the metastasis network and screen potential drugs for future treatment. Here, we identified that cell adhesion molecules and peroxisome proliferator-activated receptor (PPAR) signaling pathway were significantly enriched by analyzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Bioinformatics analysis was performed according to a previous study. [ 36 ] Additionally, a CRGs prognostic signature was constructed in PAAD patients from the TCGA cohort and validated in 2 GEO datasets. The molecular characteristics and functions of different CRGs subgroups were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis was performed according to a previous study. [ 36 ] Additionally, a CRGs prognostic signature was constructed in PAAD patients from the TCGA cohort and validated in 2 GEO datasets. The molecular characteristics and functions of different CRGs subgroups were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most-upregulated genes was Capg (gelsolin-like actin-capping protein) which was identified as poor prognostic factor for various cancers, especially liver metastasis of CRC [ 56 , 57 ]. Moreover, Apoe (Apolipoprotein E) was upregulated which is a hub gene for liver metastasis of CRC and a negative predictive factor [ 58 , 59 ]. On the contrary, strongly downregulated genes included Igfbp3 (insulin like growth factor binding protein 3) that led to downstream activation of AKT.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of bevacizumab could only increase the median overall survival time by approximately 1 to 5 months [ 45 , 46 ]. Although our previous study had performed an integrated analysis, which identified the potential hub genes serving as therapeutic targets and screened novel drugs in preventing CRC liver metastasis [ 47 ], the clinical practice is still limited. Therefore, it is necessary to further clarify the exact mechanisms of CRC metastasis and explore some novel molecules that might be applied for CRC targeted therapy.…”
Section: Discussionmentioning
confidence: 99%